2010
DOI: 10.1097/qad.0b013e3283354a7b
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive dysfunction in HIV patients despite long-standing suppression of viremia

Abstract: The prevalence of HANDs is high even in long-standing aviremic HIV-positive patients. However, HANDs without functional repercussion in daily life (asymptomatic neurocognitive impairment) is the most frequent subtype observed. In this population, the HIV dementia scale with a cutoff of 14 points or less seems to provide a useful tool to screen for the presence of HANDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
566
12
16

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 634 publications
(614 citation statements)
references
References 30 publications
20
566
12
16
Order By: Relevance
“…The results indicated that the prevalence of NCI in HIV-positive MSM in the UK was 21%, 31% or 40% depending on the standardised scoring criteria used. All these levels are much lower than those reported by previous studies, [43][44][45] and there was no difference between the deficit scores in the HIV-positive group and comparable control data from the general population or HIV-negative MSM. In addition, it was noted that large numbers of the general population would be classified as having some form of NCI based on the standard scoring criteria.…”
Section: The Antiretrovirals Sexual Transmission Risk and Attitudes contrasting
confidence: 64%
“…The results indicated that the prevalence of NCI in HIV-positive MSM in the UK was 21%, 31% or 40% depending on the standardised scoring criteria used. All these levels are much lower than those reported by previous studies, [43][44][45] and there was no difference between the deficit scores in the HIV-positive group and comparable control data from the general population or HIV-negative MSM. In addition, it was noted that large numbers of the general population would be classified as having some form of NCI based on the standard scoring criteria.…”
Section: The Antiretrovirals Sexual Transmission Risk and Attitudes contrasting
confidence: 64%
“…Neuropsychological studies have confirmed that cognitive impairment occurs in 15-50% of patients, being one of the most feared complications of HIV-1-infection. Neurocognitive impairment can also affect adherence to treatment and, ultimately, result in increased morbidity [33,34]. HIV-related neuropathology consists of microglial infiltration throughout white and grey matter, reactive astrogliosis in the cortex and in the central grey structures, and loss of neurons in the hippocampus and in the basal ganglia [35].…”
Section: Mtor and Hiv-associated Neurocognitive Disordersmentioning
confidence: 99%
“…HIV enters the CNS through infected macrophages and resides in the microglia. The number of infected glial cells in HIV patients is highly variable but generally too low to explain the underlying process of encephalitis [33,34]. Thus, it is believed that immunoinflammatory and/or degenerative responses of the microglial cells to infection rather than virus-mediated cell death can explain AIDS-related neuropathogenesis [33,34].…”
Section: Mtor and Hiv-associated Neurocognitive Disordersmentioning
confidence: 99%
“…3 Although incidence rates for HIVassociated dementia have declined, the prevalence of mild to moderate forms of cognitive dysfunction remains high, 4 with neuropsychological deficits reported in 15-50% of patients despite long-term cART and suppression of viraemia. 5 Rapid, sensitive and reliable screening tool for the presence of HIV-associated cognitive disorders are needed. Specific bedside tools such as the HIV dementia scale and the International HIV Dementia Scale have been shown to lack diagnostic effectiveness owing to inconsistencies in language comprehension and confounding clinical parameters.…”
mentioning
confidence: 99%